Loneliness and mental health: Social and clinical precisiones and ambiguites (with emphasis an periods of crisis - Alarcón-Guzmán, Renato D. (2025)
The idea and the concept of Loneliness constitute a vast field of reflections and elaborations in different areas of academic discussion. Beyond its individual and social (or collective) meanings in different languages, Loneliness is a matter of epistemological conceptualizations, artistic experiences, psychological-emotional explorations, and ontogenicphilosophical-metaphysical conceptions. Following a conceptual introductory exposition, this article centers on the several clinical implications of the term under study as a subjective state of discomfort and suffering, a symptom and/or syndrome present in a variety of nosological entities with diverse etio-pathogenic mechanisms and more or less complex modalities of therapeutic management. As a gnoseological background, its consideration as a new Social Determinant of Health and Mental Health makes of Loneliness, as well, a transcending topic of inquiries about social crises and meaningful studies of contemporary socio-cultural disciplines.